Integrated Redesign of a Fire Station in Nablus City - Abu Hatab, Raghad; Sholi, Israa; Sweedan, Jawaher (My University, 2020)
Human's life is getting complex every day. His life becomes in danger with the continuous advancement in technology and industry in different aspects in life. For that reason, it became a necessity to launch different institutions that focus on public safety through awareness, guidance and training. Our project is going to discuss the fire station of Nablus. We aim to solve all the challenges in this project and find the most appropriate solutions for such complex project. The two main challenges in such projects are architectural and mechanical aspects. In the architectural one, we will try to establish enough spaces for the fire engine functionality. In addition, we will find suitable spaces for firefighters (i.e. residence, training, etc.). In addition, different issues will be investigated such as HVAC, Plumping System and water providing system, which also influenced the structural aspects of this providing system. The methodology in this project divided into two phases. First one will focus on Architectural, Environmental and Structural analysis for the current fire station of Nablus city. Then after reviewing Architectural and based on case study standard and specifications concerns such projects, new Architectural and Structural features and proposition will be addressed. In the second phase, deep analyses based on advance simulation software will be carried out for Architectural, Structural, mechanical, electrical aspects to insure and integrated project. Finally, we hope through this process to ensure the optimum design for this project according to international standards related to such type of project.